(3n+1)(n+3)+5=40

Simple and best practice solution for (3n+1)(n+3)+5=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3n+1)(n+3)+5=40 equation:


Simplifying
(3n + 1)(n + 3) + 5 = 40

Reorder the terms:
(1 + 3n)(n + 3) + 5 = 40

Reorder the terms:
(1 + 3n)(3 + n) + 5 = 40

Multiply (1 + 3n) * (3 + n)
(1(3 + n) + 3n * (3 + n)) + 5 = 40
((3 * 1 + n * 1) + 3n * (3 + n)) + 5 = 40
((3 + 1n) + 3n * (3 + n)) + 5 = 40
(3 + 1n + (3 * 3n + n * 3n)) + 5 = 40
(3 + 1n + (9n + 3n2)) + 5 = 40

Combine like terms: 1n + 9n = 10n
(3 + 10n + 3n2) + 5 = 40

Reorder the terms:
3 + 5 + 10n + 3n2 = 40

Combine like terms: 3 + 5 = 8
8 + 10n + 3n2 = 40

Solving
8 + 10n + 3n2 = 40

Solving for variable 'n'.

Reorder the terms:
8 + -40 + 10n + 3n2 = 40 + -40

Combine like terms: 8 + -40 = -32
-32 + 10n + 3n2 = 40 + -40

Combine like terms: 40 + -40 = 0
-32 + 10n + 3n2 = 0

Factor a trinomial.
(-16 + -3n)(2 + -1n) = 0

Subproblem 1

Set the factor '(-16 + -3n)' equal to zero and attempt to solve: Simplifying -16 + -3n = 0 Solving -16 + -3n = 0 Move all terms containing n to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -3n = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -3n = 0 + 16 -3n = 0 + 16 Combine like terms: 0 + 16 = 16 -3n = 16 Divide each side by '-3'. n = -5.333333333 Simplifying n = -5.333333333

Subproblem 2

Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Divide each side by '-1'. n = 2 Simplifying n = 2

Solution

n = {-5.333333333, 2}

See similar equations:

| 7^-3/x^-2 | | 7q-13=3q+3 | | -4+3(-6n-1)=-2(-4n+5)-2 | | 5x+7.5= | | 30x-12=12x-6 | | 4y=-3.8 | | .35+3x=.45+2x | | -2y+6+3y=6 | | 5x+7(-x-10)=-82 | | 5-a=18 | | X^2-120x+3276=0 | | 4(11x-3)=-1 | | .35+3x=45+2x | | 4q+z=-9 | | -7x-4x=66 | | 3x-4=3x-5 | | 30v^3+25v^2-105v=0 | | -1/3y=11 | | 0,20=x*y-(x*y/100*5)-x | | -2(7w-4)+7w=3(w+4) | | 5/8x-5=16 | | 5/8x_5=16 | | 2x+x^2+3(4)+17= | | -4y+5+2y=7 | | -14.5+x=18.7 | | 2(2y)-5y=-4 | | -4+5+2y=7 | | -4+5+2y=y | | 2k+9=1 | | 18+9y= | | 8[5-(-6x-1)]=384x+104 | | 100=10(100) |

Equations solver categories